Implementation of Web-Based Real-Time Laundry Status Tracking System - Muhammad, Nugraha; Alfarid, Muhammad Najwan Naufal (Journal of Information Technology and Its Utilization, 2025)
The lifestyle of Indonesian society, particularly Generation Z, is characterized by a preference for practicality and a strong reliance on technology. This lifestyle pattern often reduces Generation Z’s interest in household chores, such as washing and organizing clothes. Laundry services have therefore become a popular solution, especially in urban areas. However, customers often face difficulties in monitoring the progress of their laundry in real time, leaving them uncertain whether their laundry is completed or still in process. To address this issue, this study aims to design and implement a web-based laundry status tracking system that provides customers with real-time information on their laundry progress. The system was developed using modern web technologies, employing the Laravel framework for the backend and Bootstrap for the frontend. The system also integrates additional features such as delivery and pickup options, payment methods, and progress tracking. Moreover, it provides a user-friendly interface for administrators to manage laundry data and for customers to monitor their orders. Testing results indicate that the system successfully provides accurate and real-time information, enhances transparency, and increases customer satisfaction. This system is expected to support laundry businesses in improving operational efficiency and service quality.